Evaluasi Nilai Nutrisi Jerami Padi Direct dan Indirect dengan Metode Amoniasi dan Fermentasi (Amofer) sebagai Pakan Ternak: Evaluation of the Nutritional Value of Rice Straw through Direct and Indirect Methods using Ammoniation and Fermentation (Amofer) as Livestock Feed - Fridayati, Diah; Al Adam, Koji; Raudhah, Raudhah; Fatmala, Nanda; Risna, Yayuk Kurnia (Fakultas Peternakan Universitas Jambi, 2024)
Background: The widespread burning of rice straw has caused significant air pollution. Purpose: This study aims to utilize rice straw as livestock feed through indirect ammoniation and fermentation technology, considering the duration of fermentation. Methods: The research was conducted at the MIPA Laboratory of Almuslim University and the BSPJI Banda Aceh Laboratory, from 01 June – 23 August 2024. The study used rice straw waste and employed a Completely Randomized Design (CRD) consisting of 4 treatments with 3 replications each. The treatments included P0 (Control/no treatment), P1 (7 days of fermentation), P2 (14 days of fermentation), and P3 (21 days of fermentation). The observed parameters were crude protein and crude fat content. The data obtained were analyzed using Analysis of Variance (ANOVA). Results: The average value of crude protein percentage obtained from direct and indirect methods obtained the highest value in treatment P3, namely 11.12 and 7.14, while the lowest value in treatment P0, namely 7.92 and 4.86. The average value of crude fat percentage obtained from direct and indirect methods obtained the highest value in treatment P3, namely 1.71 and 1.51, while the lowest value in treatment P0, namely 1.09 and 1.44. Conclusion: From the results above, it can be concluded that rice straw amofer has a significant indirect effect (P>0.05) on crude protein levels.